2013
DOI: 10.1039/c3lc41232f
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced energy conversion from the streaming current by polymer addition

Abstract: In this contribution, we present for the first time the experimental results of energy conversion from the streaming current when a polymer is added to the working solution. We added polyacrylic acid (PAA) in concentrations of 200 ppm to 4000 ppm to a KCl solution. By introducing PAA, the input power, which is the product of volumetric flow rate and the applied pressure, reduced rapidly as compared to the case of using only a normal viscous electrolyte KCl solution. The output power at the same time remained l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 35 publications
0
45
1
Order By: Relevance
“…It is clear that the FCL ions of the so nanochannel contribute to this massive enhancement of the efficiency -therefore, decrease in the relative thickness of the FCL (which in turn will imply larger number of FCL ions, since the number density of the FCL ions is constant) increases the value of the ratio x S /x H . As discussed previously, this enhancement, unlike certain recent studies, 38,39 is not an articial one caused by consideration of a lower input power P in ; rather it is solely caused by the presence of additional charges of the FCL. This result indicates a possibility where the nanouidic streaming-current-mediated energy conversion efficiency can be increased several folds by using a so nanochannel, or a nanochannel that contains a polymer layer graed onto its surface.…”
Section: Resultscontrasting
confidence: 60%
“…It is clear that the FCL ions of the so nanochannel contribute to this massive enhancement of the efficiency -therefore, decrease in the relative thickness of the FCL (which in turn will imply larger number of FCL ions, since the number density of the FCL ions is constant) increases the value of the ratio x S /x H . As discussed previously, this enhancement, unlike certain recent studies, 38,39 is not an articial one caused by consideration of a lower input power P in ; rather it is solely caused by the presence of additional charges of the FCL. This result indicates a possibility where the nanouidic streaming-current-mediated energy conversion efficiency can be increased several folds by using a so nanochannel, or a nanochannel that contains a polymer layer graed onto its surface.…”
Section: Resultscontrasting
confidence: 60%
“…As a result, the solution viscosity in these layers increases, suggested as "chargeinduced thickening" effects by Bazant et al 6,70 Interestingly, one may harness the streaming current and the streaming potential to drive current through an external resistor, thereby converting mechanical (hydraulic) energy into electrical energy. [71][72][73][74][75][76][77][78] There have been several promising theoretical analyses and experimental demonstrations of electrokinetic effects and energy conversion in micro-and nanopores, exploiting streaming potential phenomenon. 15,76,[78][79][80] However, analytical representation of electrokinetic effects in combined presence of steric interactions and charge induced thickening appears to be a difficult proposition, primarily because of the inherent nonlinearity in the underlying phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that time periodic electro-osmotic flow in many cases is much stronger enhanced than time periodic pressure-driven flow when comparing the flow profiles of oscillating PDF and EOF in micro-and nanochannels. The findings advance our understanding of time periodic electrokinetic phenomena of viscoelastic fluids and provide (Nguyen et al 2013). Chakraborty and colleagues have theoretically studied transport of non-Newtonian fluid (inelastic power law fluids and recently viscoelastic constitutions) using separately steady PDF (Bandopadhyay and Chakraborty 2011), steady EOF (Chakraborty 2007;Ghosh and Chakraborty 2015), time periodic PDF (Bandopadhyay and Chakraborty 2012a, b;Bandopadhyay et al 2014) and time periodic EOF (Bandopadhyay et al 2013) in rectangular narrow confinements.…”
Section: Introductionmentioning
confidence: 99%